Pengaruh Faktor Demografi, Sosial dan Ekonomi terhadap Financial Sustainability Pemerintah Daerah: Studi Empiris pada Kabupaten/Kota di Indonesia - Sari, Diah Permata; Sari, Vita Fitria (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of demographic, social, and economic factors on the financial sustainability of local governments in Indonesia. This empirical study, conducted in districts/cities in 2022, intends to answer research questions related to the influence of demographic, social, and economic factors on financial sustainability. This research has a novelty by adding social factors in testing their influence on financial sustainability. The sampling technique was carried out using purposive sampling, with the multiple regression analysis method assisted by the SPSS version 25 program. The results showed that of the seven variables studied, three variables showed a significant influence on financial sustainability, namely population, GRDP, and investment level. Meanwhile, other variables such as population density, population age below 15 years, population age above 65 years, and education level did not show a significant influence on financial sustainability. The findings of this study make an important contribution to understanding the factors that influence the financial sustainability of local governments in Indonesia.